2015
DOI: 10.3390/ijerph120403439
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Levels and Presence of Selected Tobacco-Derived Toxins in Tobacco Flavoured Electronic Cigarette Refill Liquids

Abstract: Background. Some electronic cigarette (EC) liquids of tobacco flavour contain extracts of cured tobacco leaves produced by a process of solvent extraction and steeping. These are commonly called Natural Extract of Tobacco (NET) liquids. The purpose of the study was to evaluate nicotine levels and the presence of tobacco-derived toxins in tobacco-flavoured conventional and NET liquids. Methods. Twenty-one samples (10 conventional and 11 NET liquids) were obtained from the US and Greek market. Nicotine levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 27 publications
7
96
0
Order By: Relevance
“…[17,18] An earlier study by Trehy et al [9] observed that nicotine content labeling issues were also present with most of the products they tested. While some studies have reported nicotine levels higher than label claims (e.g., Trehy et al [9] and Farsalinos et al [19] ), consistent with Lisko et al, [6] for the samples measured in this study, all nicotine values were lower than reported values. Laugesen et al [20] also observed differences between labeled and measured nicotine concentration, and they concluded that these differences were due to a "lack of quality control."…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…[17,18] An earlier study by Trehy et al [9] observed that nicotine content labeling issues were also present with most of the products they tested. While some studies have reported nicotine levels higher than label claims (e.g., Trehy et al [9] and Farsalinos et al [19] ), consistent with Lisko et al, [6] for the samples measured in this study, all nicotine values were lower than reported values. Laugesen et al [20] also observed differences between labeled and measured nicotine concentration, and they concluded that these differences were due to a "lack of quality control."…”
Section: Resultssupporting
confidence: 55%
“…Nicotine levels were also evaluated in the commercial products to confirm label claims and, consistent with previously published results, inconsistencies were observed for some products. [6,9,18,19,21,22] Most products were within 30% of the label claim, while others exceeded 50%. Using the targeted method described herein using MS with MRM, it was possible to achieve the sensitivity necessary to detect most of the nicotine-related impurities in all the commercial products tested.…”
Section: Discussionmentioning
confidence: 99%
“…We selected these constituents because they have been found to be present in novel tobacco products. [4][5][6][7][8] Participants were shown a list of these constituents and asked whether they had heard of or knew anything about each constituent. Participants were also asked what they would like to know about these constituents.…”
Section: Methodsmentioning
confidence: 99%
“…Since the focus groups were conducted, new research has continued to expand the list of constituents found in novel tobacco products and their smoke or aerosol, especially for e-cigarettes. 4,5…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation